2008
DOI: 10.1002/adsc.200700519
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Aziridination Reactions

Abstract: A small quantity of iron(II) triflate (2.5 to 5 mol%) catalyzes the aziridination reactions of enol silyl ethers with tosyliminoA C H T U N G T R E N N U N G (iodo)benzene (PhINTs) in acetonitrile to give a-N-tosylamido ketones by subsequent aziridine ring opening. Olefins are converted into aziridines by 5 mol% of this catalyst system. Both reactions afford the corresponding products in moderate to good yields. In the presence of chiral ligands asymmetric aziridinations have been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(53 citation statements)
references
References 82 publications
1
52
0
Order By: Relevance
“…was also reported by Bolm and co-workers [33] in the presence of a simple iron salt Fe(OTf) 2 (Scheme 14). The in situ generated iminoiodianes from the mixtures of the corresponding sulfonamide and PhI(OAc) 2 made this reaction a variation of the aforementioned aziridination of PhINTs with alkenes [34].…”
Section: Methodsmentioning
confidence: 57%
“…was also reported by Bolm and co-workers [33] in the presence of a simple iron salt Fe(OTf) 2 (Scheme 14). The in situ generated iminoiodianes from the mixtures of the corresponding sulfonamide and PhI(OAc) 2 made this reaction a variation of the aforementioned aziridination of PhINTs with alkenes [34].…”
Section: Methodsmentioning
confidence: 57%
“…On the other hand, Che and co‐workers showed that alkene aziridination in the presence of [Fe(Cl 3 terpy) 2 ] 34 (Cl 3 terpy = 4,4′,4″‐tri‐ tert ‐butyl‐2,2′:6′2″‐terpyridine, Figure 2f) as catalyst was applicable to a wider range of starting alkenes and gave the corresponding products in 68–97% yield (Table 2, entry 12) 29. This work was followed by a report by Bolm and co‐workers, who demonstrated a Fe(OTf) 2 ‐catalyzed version of this reaction that gave the corresponding products in moderate to good yields of 24–90% (Table 2, entry 13) 30…”
Section: Intermolecular Aziridination Of Alkenes With Phintsmentioning
confidence: 86%
“…Bolm and co‐workers demonstrated that an iron(II)‐catalyzed version of this process could also be accomplished 30. When the substrates 53 were exposed to Fe(OTf) 2 and PhINTs, the corresponding α‐amino ketones 55 were attained in moderate to good yields of 46–72%.…”
Section: Intermolecular Aziridination Of Silyl Enol Ethersmentioning
confidence: 99%
“…The filtrate was removed under reduced pressure to obtain the crude product, which was further purified by silica gel chromatography (petroleum/ethyl acetate = 10/1 as eluent) to yield corresponding product. The identity and purity of the products was confirmed by 1 H and 13 C NMR spectroscopic analysis.…”
Section: Methodsmentioning
confidence: 99%